AKTIVITAS ANTIBAKTERI DARI FRAKSI DAUN KATUK HUTAN (Breynia cernua) ASAL PAPUA: ANTIBACTERIAL ACTIVITY OF FRACTION KATUK HUTAN LEAF (Breynia cernua) FROM PAPUA - Ishariyanto, Riski; Dirgantara, Septriyanto; Susanto, Sharon; Septiana, Rita (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Abstract Katuk hutan leaf (Breynia cernua) are endemic plants of Papua traditionally used to treat cancer, smallpox and wounds. It contains various bioactive compounds such as alkaloids, flavonoids, terpenoids and tannins. Fractionation using n-hexane, ethyl acetate and ethanol-water solvents was performed to isolate specific bioactive components. This study aims to evaluate the antibacterial activity of n-hexane fraction, ethyl acetate fraction and ethanol-water fraction of Breynia cernua leaf against Staphylococcus aureus and Escherichia coli. Antibacterial testing was conducted using the disc diffusion method at concentrations of 250, 500 and 750 ppm. All fractions exhibited inhibition zones in the moderate to strong category against both bacteria. The highest antibacterial activity was observed in the n-hexane fraction at 750 ppm with inhibition zone of 10.2 ± 0.8 mm for S. aureus and 10.3 ± 0.8 mm for E. coli. ANOVA analysis showed a significant difference (p < 0.05) between the n-hexane fraction and the other fractions. These results indicate that the n-hexane fraction of Breynia cernua leaves has the most potent antibacterial effect. Keywords: Breynia cernua, disc diffusion, inhibition zone, Staphylococcus aureus, Escherichia coli.